THE INTEGRATION OF WEB-BASED LEARNING MEDIA INTO ELT: USING WEBQUEST TO ENHANCE STUDENTS’ WRITING ACHIEVEMENT - Ira Irzawati; Anastasia Ronauli Hasibuan (Jurnal Didascein Bahasa, 2019)
In recent decades, the integration of web-based learning media into English Language Teaching (ELT) has become an ideal choice for the educators to support students’ success in learning English. This research presents the use of a web-based learning medium (Webquest) to enhance students’ writing achievement. It involved sixty-two of eleventh grade students which divided into two groups; experimental and control groups. The researchers applied Webquest in experimental class to investigate whether the integration of Webquest into teaching and learning activities was effective or not to improve students’ writing achievement. To collect the data, writing test in form of essaywas administered to both groups. The data were analyzed by using independent and pair t-tests. The results revealed that the experimental group students’ writing achievement outperformed the control group students’ writing achievement. In a nutshell, it is believed that Webquest is an effective learning tool to improve students’ writing achievement.